2019
DOI: 10.3389/fpsyt.2018.00752
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neuroinflammation in Postoperative Cognitive Dysfunction: Moving From Hypothesis to Treatment

Abstract: Postoperative cognitive dysfunction (POCD) is a common complication of the surgical experience and is common in the elderly and patients with preexisting neurocognitive disorders. Animal and human studies suggest that neuroinflammation from either surgery or anesthesia is a major contributor to the development of POCD. Moreover, a large and growing body of literature has focused on identifying potential risk factors for the development of POCD, as well as identifying candidate treatments based on the neuroinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
228
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(233 citation statements)
references
References 216 publications
1
228
0
4
Order By: Relevance
“…Evidence suggests that neuroinflammation after surgery plays a key role in postoperative cognitive dysfunction and perioperative neurocognitive disorder. 84,85 The preexisting vulnerabilities mentioned above are thought to increase blood brain barrier permeability, 86 and allow the peripheral innate immune molecules, generated by surgical tissue damage, to enter the central nervous system to further enhance neuroinflammation and injury. Moreover, mice that lack genes to mount significant neuroinflammation did not develop postoperative cognitive dysfunction after anesthesia and surgery.…”
Section: Rodents (Mice and Rats)mentioning
confidence: 99%
“…Evidence suggests that neuroinflammation after surgery plays a key role in postoperative cognitive dysfunction and perioperative neurocognitive disorder. 84,85 The preexisting vulnerabilities mentioned above are thought to increase blood brain barrier permeability, 86 and allow the peripheral innate immune molecules, generated by surgical tissue damage, to enter the central nervous system to further enhance neuroinflammation and injury. Moreover, mice that lack genes to mount significant neuroinflammation did not develop postoperative cognitive dysfunction after anesthesia and surgery.…”
Section: Rodents (Mice and Rats)mentioning
confidence: 99%
“…It is commonly suggested that hippocampal-dependent learning and memory are degraded in aged rodents and humans (Daugherty and Raz 2017; Kadish et al 2009). Clinically meaningful disruptions in spatial learning and memory (e.g., a loss of goal location based on surrounding landmarks) are also associated with repeated anesthesia, such as isoflurane, a common experience for the older patient (Culley et al 2003;Lin and Zuo 2011;Safavynia and Goldstein 2019). The spatial confusion in these apparently disparate conditions is commonly proposed to stem from oxidative stress within the mid-and posterior hippocampus (HC, human), or dorsal CA1 (CA1, rodents), which are specialized sub-regions of brain essential for encoding spatial information (Ali et al 2006;Arimon et al 2015;Chen et al 2014;Fanelli et al 2013;Forster et al 1996;Frisoni et al 2008;Hall et al 2012;Han et al 2015;Kanamaru et al 2015;McManus et al 2011;Moser et al 1993;Mueller et al 2007;Navarro et al 2008;Nicolle et al 2001;Pratico et al 2001;Raz and Daugherty 2018;Strange et al 2014;Tucsek et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…NPD1 shares biological activities with other lipid mediators such as resolvins and maresins, including accelerating nonphlogistic macrophage phagocytosis, inhibiting neutrophil infiltration, and regulating the production of cytokines and chemokines (Serhan et al, 2002;Mukherjee et al, 2004;Hong et al, 2014). Additionally, NPD1 has been demonstrated to be neuroprotective in preclinical models of Alzheimer's disease, which shares some characteristics with POD, such as memory impairment (Lukiw et al, 2005;Safavynia and Goldstein, 2019).…”
Section: Introductionmentioning
confidence: 99%